Transport Properties of Diethyl Malonate with Aniline and Benzaldehyde at 308.15 and 318.15 K - Prabhu, P.; Revathy, U.; Venis, A. Rose (Asian Journal of Chemistry, 2018)
Densities, viscosities and ultrasonic velocities of binary liquid mixtures of diethyl malonate with aniline and benzaldehyde have been measured at 308.15 and 318.15 K. From these data, excess volume (VE), deviation in isentropic compressibility (ΔKS), deviation in viscosity (Δη), deviation in intermolecular free length (ΔLf), deviation in free volume (ΔVf), deviation in internal pressure (Δπi) and deviation in acoustic impedance (ΔZ) have been calculated. These results were correlated with the Redlich and Kister type polynomial equation to derive the coefficients and standard errors. Variations in the calculated excess quantities have been studied for mixtures of diethyl malonate with component liquids. From the value of excess properties, intermolecular interactions have been studied.